Trade Effects of the East African Community: Do We Need a Transitional Fund? - Matthias Busse; Rasul Shams (Hamburg Institute of International Economics (HWWA), 2003)
The paper evaluates the economic necessity and political incentives of a transitional fund for the East African Community (EAC). The fund has been proposed to encounter trade imbalances which may arise due to the intended customs union in East Africa. Using a disaggregated approach at the two-digit level of the Standard International Trade Classification, the paper assesses the overall impact of the EAC on trade flows. Moreover, the commodities that will be particularly affected by the customs union are identified. The results show that considerable trade effects cannot be expected, except for a very narrow range of products. The need for a transitional fund becomes less urgent from this perspective.
Keywords: F15; F17; 330; Customs Union; EAC; Kenya; Tanzania; Uganda; Zollunion; Außenhandelseffekt; Handelsbilanz; Zahlungsbilanzungleichgewicht; Ostafrika